2019
DOI: 10.1128/jb.00231-19
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Aged Spores of Bacillus subtilis

Abstract: Bacillus spores incubated on plates for 2 to 98 days at 37°C had identical Ca-dipicolinic acid contents, exhibited identical viability on rich-or poor-medium plates, germinated identically in liquid with all germinants tested, identically returned to vegetative growth in rich or minimal medium, and exhibited essentially identical resistance to dry heat and similar resistance to UV radiation. However, the oldest spores had a lower core water content and significantly higher wet heat and NaOCl resistance. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…S3). However, as noted in the text, the spore H-Mn(Pi) component of the spectrum includes contributions not only from Mn complexed with inorganic phosphate (Pi) but also from the similar spectra of Mn complexed with the large amounts of 3-phosphoglyceric acid found in spores of all Bacillus species examined, in some cases with levels even higher than Pi (Camilleri et al, 2019 ; Ghosh et al, 2011 ). ( C ) Survival of B. megaterium (QMB1551) spores and vegetative cells irradiated as in (A).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…S3). However, as noted in the text, the spore H-Mn(Pi) component of the spectrum includes contributions not only from Mn complexed with inorganic phosphate (Pi) but also from the similar spectra of Mn complexed with the large amounts of 3-phosphoglyceric acid found in spores of all Bacillus species examined, in some cases with levels even higher than Pi (Camilleri et al, 2019 ; Ghosh et al, 2011 ). ( C ) Survival of B. megaterium (QMB1551) spores and vegetative cells irradiated as in (A).…”
Section: Resultsmentioning
confidence: 97%
“…S2, left). Taking into consideration the high abundance of dipicolinic acid (DPA) in spores, but not in vegetative cells (Granger et al, 2011 ; Camilleri et al, 2019 ), we treated, for consistency, the H-Mn signal in the spores as a weighted sum of Mn-Pi and Mn-DPA spectra, but in the vegetative cells as a sum of Mn-Pi and Mn-Imi spectra, while emphasizing that reversal of the procedure showed that the choice has no influence on any conclusions (see Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…Ruling this out is most likely impossible. However, a simple experiment of leaving spores to sporulate for different times, and then analyzing their mRNA levels provided strong evidence that spore mRNAs, more specifically intact spore mRNAs, are not essential for at least B. subtilis spore germination and outgrowth (Camilleri et al, 2019). Thus RNA-Seq analysis on B. subtilis spores harvested after 2 days of sporulation gave approximately the same ~50 spore mRNAs at ≥1 molecule/ spore, but spores allowed to sporulate on plates for 45-90 days at 37°C gave RNA from which levels of all spore mRNAs were decreased ≥95-fold, and rRNAs were significantly fragmented.…”
Section: The Smoke Begins To Clearmentioning
confidence: 99%
“…The second major evidence against any essential involvement of macromolecular synthesis in spore germination is that ATP levels are almost non-existent in dormant spores, and appear to increase only after germination is complete (Setlow and Kornberg, 1970a;Scott and Ellar, 1978). While this result is potentially definitive in ruling out macromolecular synthesis' involvement in spore germination, this experiment can be confounded to some extent by at least three factors -(i) the heterogeneity in germination rates between individual spores in populations (Setlow et al, 2017), so that curves for both germination and ATP accumulation are broadened significantly, (ii) completion of germination after CaDPA release requires hydrolysis of the spore cortex peptidoglycan, which leads to an increase in core water content to 80% of wet wt allowing full protein mobility in spores and thus metabolic activity; however, the latter increase in core water is not rapid and takes 10-15 min in B. subtilis (Camilleri et al, 2019), and perhaps there could be metabolic activity when core water content reaches 60% of wet wt, and (iii) analyses of the accumulation of ATP by germinating spores has always been measured by extraction of small molecules and subsequent analyses and it would be ideal to measure molecules such as ATP, NADH, etc., in individual germinating spores, as this would give much higher resolution for analyses of when ATP and other high energy compounds were generated in spore germination. Indeed, certainly our understanding of spore germination has been significantly increased by examining the germination of multiple individual spores (Setlow et al, 2017).…”
Section: Issues For the Futurementioning
confidence: 99%
See 1 more Smart Citation